The antiinflammatory and electrophysiological effects of fingolimod on penicillin-induced rats - Türel, Canan Akünal; Çelik, Hümeyra; Torun, İbrahim Ethem; Çetinkaya, Ayhan; Türel, İdris (Arquivos de Neuro-Psiquiatria, 2022)
Background The fact that inflammation triggers epileptic seizures brings to mind the antiepileptic properties of anti-inflammatory drugs.Objective To investigate the electrophysiological and anti-inflammatory effects of fingolimod on an experimental penicillin-induced acute epileptic seizure model in rats.Methods Thirty-two male Wistar rats were divided into four groups: control (penicillin), positive control (penicillin + diazepam [5 mg/kg]), drug (penicillin + fingolimod [0.3 mg/kg]) and synergy group (penicillin + diazepam + fingolimod). The animals were anesthetized with urethane, and epileptiform activity was induced by intracortical injection of penicillin (500,000 IU). After electrophysiological recording for 125 minutes, IL-1β, TNF-α, and IL-6 were evaluated by ELISA in the serum of sacrificed animals.Results During the experiment, animal deaths occurred in the synergy group due to the synergistic negative chronotropic effect of diazepam and fingolimod. Although not statistically significant, fingolimod caused a slight decrease in spike-wave activity and spike amplitudes in the acute seizure model induced by penicillin (p > 0.05). Fingolimod decreased serum IL-1β (p < 0.05); fingolimod and diazepam together reduced IL-6 (p < 0.05), but no change was observed in serum TNF-α values.Conclusion Even in acute use, the spike-wave and amplitude values of fingolimod decrease with diazepam, anticonvulsant and anti-inflammatory effects of fingolimod will be more prominent in chronic applications and central tissue evaluations. In addition, concomitant use of fingolimod and diazepam is considered to be contraindicated due to the synergistic negative inotropic effect.
Keywords: Rats; Fingolimod Hydrochloride; Anti-Inflammatory Agents; Electrophysiology; Seizures; Epilepsy; Penicillins